2014
DOI: 10.1136/bmjopen-2014-005045
|View full text |Cite
|
Sign up to set email alerts
|

Doing challenging research studies in a patient-centred way: a qualitative study to inform a randomised controlled trial in the paediatric emergency care setting

Abstract: ObjectiveTo inform the design of a randomised controlled trial (called EcLiPSE) to improve the treatment of children with convulsive status epilepticus (CSE). EcLiPSE requires the use of a controversial deferred consent process.DesignQualitative interview and focus group study.Setting8 UK support groups for parents of children who have chronic or acute health conditions and experience of paediatric emergency care.Participants17 parents, of whom 11 participated in telephone interviews (10 mothers, 1 father) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
115
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 55 publications
10
115
0
Order By: Relevance
“…However, our results are consistent with other evidence indicating the acceptability of deferred consent to parents and to practitioners with experience of the process. 13,19,20 The higher consent rate for emergency compared with elective admissions may reflect a greater capacity for informed decision-making when parents were approached after the medical emergency had taken place, in a potentially less stressful environment. For elective admissions, parents may have felt responsible for…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are consistent with other evidence indicating the acceptability of deferred consent to parents and to practitioners with experience of the process. 13,19,20 The higher consent rate for emergency compared with elective admissions may reflect a greater capacity for informed decision-making when parents were approached after the medical emergency had taken place, in a potentially less stressful environment. For elective admissions, parents may have felt responsible for…”
Section: Discussionmentioning
confidence: 99%
“…19,22 In CATCH, decisions on timing of approach for consent after bereavement depended on the circumstances around the death and how well the team knew the family. Up to 2 telephone or mail reminders were sent to those who did not respond.…”
Section: Figurementioning
confidence: 99%
“…They also advocated taking permission for deferred telephone consent from IRBs in minimal-risk studies that need a telephone follow-up. Woolfall et al (2014) found that most of the subjects who represented patients were unfamiliar with deferred consent, but responded positively to a general description of the method. Trust in practitioners for their capability in making research-related decisions is an important factor associated with positive responses.…”
Section: Deferred Consentmentioning
confidence: 94%
“…Research suggests that parents favour deferred consent over waived consent and consider it an acceptable alternative to informed consent for emergency situations [59,60]. In a study by Woolfall et al [60], parents suggested it would be advisable for the researchers to seek advice from the bedside nurse to establish the moment when the child's condition was stable and then ask for consent.…”
Section: Deferred Consentmentioning
confidence: 97%
“…In a study by Woolfall et al [60], parents suggested it would be advisable for the researchers to seek advice from the bedside nurse to establish the moment when the child's condition was stable and then ask for consent. Practitioners with experience in asking for deferred consent were generally positive about parental acceptance of this method of consent.…”
Section: Deferred Consentmentioning
confidence: 99%